Encapsulation of Old Tailings Deposits from Morro Velho Gold Mining in Minas Gerais, Brazil - Alves, AF; Braga, I; Pós, W (Mine Closure 2008: Third International Seminar on Mine Closure, 2008)
Nova Lima, hometown of the AngloGold Ashanti operation in the state of Minas Gerais, Brazil, has been a gold centre since 1834. At that time, the tailings were dumped directly into local rivers and streams. Since the 1930s, however, tailings at the Morro Velho Mining operations began to be deposited along the banks of the Cardoso River, amounting to one million m3 of tailings being spread over 250,000 m2. Included in these tailings is arsenic, at a concentration of approximately 20,000 mg/kg. Since 1985, tailings have been disposed of at a properly-engineered tailings impoundment. To address the potential hazard associated with the older tailings deposits, a risk assessment was conducted. The assessment included a hydrogeologic and geochemical study, as well as a global risk analysis. The findings indicated that encapsulation of tailings would be required in order to minimize the future risk of human exposure. The main criteria for technology selection was that it provided the highest environmental and health protection for the local area and its residents. As a result, a clean-up and encapsulation process commenced in May 2003 with the rehabilitation of Morro do Galo, an old arsenic trioxide recovery plant, which was completed in December 2003. The second site to be addressed was the Galo tailings deposit in 2004, followed by Resende and Matadouro tailings deposits in 2006 and 2007. Up to 2008, approximately US$ 3.5 million had been spent on these projects, and encapsulation of the remaining old tailings deposits is planned to commence next year, in 2009. All the rehabilitation work completed to date has received the endorsement of the Brazilian Environmental Authorities, and the encapsulation has resulted in a significant decrease in the mean arsenic concentration of the shallow groundwater in contact with the old tailings. This case study demonstrates how AngloGold Ashanti Mineração Brazil has addressed a challenging legacy of contamination, in partnership with environmental authorities and the local community. This kind of intervention demonstrates that it is possible to undertake the rehabilitation of old tailings deposits in a populated area safely, without the relocation of residents.